2022
DOI: 10.5812/jhealthscope-119063
|View full text |Cite
|
Sign up to set email alerts
|

At-risk COVID-19 Patients; Knowledge and Attitude of Those in Need of Transfer to Hospital and Consequences in Non-transferred Patients

Abstract: Background: Knowledge, attitude, and practice of people, especially high-risk ones, are essential for managing COVID-19. Previous studies have shown that inappropriate knowledge and attitude may influence people's decisions. Objectives: This study aimed to evaluate the knowledge and attitudes of patients towards COVID-19 who called emergency medical service (EMS) while suffering from a chronic underlying disease, whether they were transferred to the hospital during the pandemic or not. Methods: This cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…According to previous documents, 80% of skin manifestations turn back to inflammatory reactions caused by COVID-19. These symptoms are mainly manifested in the form of erythema, pruritus, and vesicles in most of the patients (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…According to previous documents, 80% of skin manifestations turn back to inflammatory reactions caused by COVID-19. These symptoms are mainly manifested in the form of erythema, pruritus, and vesicles in most of the patients (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Increased expression of miR-106b-5p and miR-26b-5p leads to disease progression. The study of several patients with leukaemia has shown the key role of miR-26b-5p in leukaemia ( 40 42 ). Its increased expression leads to the inhibition of the TGF-B/SMAD signalling pathway, which results in down expression of P21-G1P1kinase inhibitor and high expression of c-MYC oncogene.…”
Section: Introductionmentioning
confidence: 99%
“… 3 Remote visit with communication equipment is a part of telemedicine, which is helpful for vulnerable people and also for following up on the treatment of patients with chronic diseases. 4 The simplest method of providing remote health services is using a phone for consultations. Although it has weaknesses, such as the lack of visual information, it is getting attention due to the ease of implementation, significant effects on reducing costs and unnecessary referrals, and improved access to care.…”
Section: Introductionmentioning
confidence: 99%